Quality of experience provisioned mobile streaming protocol for the hyper-connected Internet of Things devices over the heterogeneous wireless access networks - Min Ho Park; Jun Kyun Choi; JungYul Choi (International Journal of Distributed Sensor Networks)
5G-based hyper-connected Internet of Things environment is emerging, where various connectivities such as BlueTooth, WiFi, and 3/4/5G are provided. Since they have different communication characteristics, it is difficult to provide the user quality of experience when the handoff takes place according to the movement of the mobile devices between wireless access networks. For solving this problem, we propose a seamless video streaming protocol to satisfy the user quality of experience regardless of handoff. The proposed protocol can dynamically adjust streaming bit rate according to the network condition and also maintain fixed quantity of buffered audio–video data for the stable quality of experience level. The proposed protocol is designed independently of OS versions and CPU performance of terminals, which makes it easy to be implanted in various types of Internet of Things devices. Real-world experimental results show that seamless video streaming service can be guaranteed by carefully predicting the network dynamics over the heterogeneous wireless access networks. The protocol is now commercially deployed for over 5 million Long-Term Evolution subscribers of a South Korea telco, LG U+.